Fractures at Diagnosis in Infants and Children with Osteogenesis Imperfecta - Greeley, Christopher Spencer (2013)
BACKGROUND: In infants and children with fractures from an unclear cause, Osteogenesis Imperfecta (OI) is often included as a potential etiology. In infants and children with OI there exists a gap in the published literature regarding the fracture pattern seen at the time of diagnosis. As an additional aid to the diagnosis of OI, we sought to characterize the fracture patterns in infants and children at the time of their diagnosis. METHODS: We performed a retrospective chart review of a series of infants and children under 18 years of age who have the diagnosis of OI (any type) from a single institution. RESULTS: We identified 68 infants and children with OI: 23 (34%) type 1, 1(2%) type 2, 17(25%) type 3, 24(35%) type 4 and 3(4%) unknown type. A family history of OI is present in 46% of children. Forty-nine (72.0%) patients were diagnosed solely on clinical characteristics, without genetic or fibroblast confirmation. Rib fractures were noted in 21% of the subjects with none being identified during infancy. The number of fractures identified at diagnosis ranged from 1 to >37 with 7 (10%) having more than 2 fractures. All subjects with more than 2 fractures were diagnosed prenatally or in the immediate newborn period. Seventeen (25%) infants were diagnosed after 1 week of age but prior to 12 months of age. None of these infants had either rib fractures or more than 1 fracture at the time of diagnosis. CONCLUSION: The majority of children diagnosed with OI are diagnosed by clinical features alone. The fracture pattern at the time of diagnosis in OI is variable with 10% having more than 2 fractures. The diagnosis of OI was made in utero or at delivery in 43% of children. Multiple rib fractures in an infant would be an unexpected finding in OI. LEVEL OF EVIDENCE: Level III